Opposite Effect of Social Evaluation on Creative Idea Generation in Early and Middle Adolescents. Issue 4 (2nd October 2021) - Camarda, Anaëlle; Bouhours, Lison; Osmont, Anaïs; Le Masson, Pascal; Weil, Benoît; Borst, Grégoire; Cassotti, Mathieu
ABSTRACT: The aim of the present study was to examine how social evaluation influences creative idea generation, and whether this effect develops with age. To do so, early adolescents, middle adolescents, and late adolescents performed a creative task either alone or under the supervision of an adult examiner. Three major findings emerged: 1) the social evaluation by an adult expert is detrimental to creativity in children but 2) beneficial in adolescence, while 3) it has no effect on late adolescents. The present study is the first to provide evidence that social evaluation by an adult has an opposite effect on creative idea generation in children and adolescents, and offers new directions to investigate social influences on creativity from a developmental perspective.